1967
DOI: 10.1063/1.1705281
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Three-Body Problem

Abstract: The three-body problem in one dimension is examined to determine for what class of interactions the Schrödinger equation may be solved by separation of variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…It is obvious to see that this potential is the sum of the harmonic oscillator and inversely quadratic potential. Hurley found that this kind of pseudoharmonic oscillator interaction between the particles can be exactly solved when he studied three-body problem in one dimension [198]. Since 1961 such a quantum system has been studied by many authors [2,[195][196][197][198][199][200][201][202][203][204][205][206][207][208][209].…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious to see that this potential is the sum of the harmonic oscillator and inversely quadratic potential. Hurley found that this kind of pseudoharmonic oscillator interaction between the particles can be exactly solved when he studied three-body problem in one dimension [198]. Since 1961 such a quantum system has been studied by many authors [2,[195][196][197][198][199][200][201][202][203][204][205][206][207][208][209].…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of the pseudo-harmonic potential have been considered for improvements in the conventional presentation of molecular vibrations75. Hurley found that this kind of PHO interaction between the particles can be exactly solved by the separation of variables while studying the three-body problem in one dimension76. A few years later, Calogero studied the one-dimensional three- and N-body problems interacting pairwise via harmonic and inverse square (centrifugal) potential7778.…”
Section: Parity Deformed Jcm and Interpretationmentioning
confidence: 99%
“…Por exemplo, Landau e Lifshitz determinaram as soluções exatas da equação de Schrödinger para uma partícula em um potencial pseudo-harmônico em três dimensões [3]. Hurley considerou este potencial para estudar o problema de três corpos em uma dimensão [4]. Calogero abordou o problema de N corpos interagindo através de um potencial pseudo-harmônico [5,6].…”
Section: Introductionunclassified